Pencatatan Akuntansi Sesuai Aturan Perpajakan Guna Memanfaatkan Insentif Perpajakan - Danang Adi Putra; Nikmah Nikmah; Lismawati Lismawati; Fachruzzaman Fachruzzaman; Deasy Emalia; Nurul Qomariah (BADAN PENERBIT STIEPARI PRESS, 2025)
This study aims to enhance the understanding of tax regulations among Small and Medium Enterprises (SMEs) in Bengkulu, Indonesia, and provide guidance on utilizing tax incentives through proper accounting practices. The research was conducted through a community service program for Liquid Fotocopy SME in Bengkulu, involving training sessions and direct mentoring to teach simple accounting methods for tax compliance. Workshops, surveys, and feedback mechanisms were employed to assess participants' comprehension of accounting and tax obligations. The study found significant improvement in participants' knowledge and skills in managing their businesses, particularly through practical accounting practices, which boosted their motivation and confidence. This enabled them to implement accurate tax calculations, especially once their revenue surpassed the personal tax allowance (PTKP). The findings highlight that training SMEs in basic accounting and tax regulations is crucial for improving financial management and complying with tax obligations. The study is limited to one SME in Bengkulu, with no consideration for regional variations or challenges faced by other SMEs in Indonesia.